Федір Андрійович Лизогуб (1851 – 1928) (до 165-річчя з дня народження) - Половець, В. (Сiверянський лiтопис, 2016)
Стаття присвячена Федору Андрійовичу Лизогубу – українському політичному
і громадському діячеві та меценату, голові Ради Міністрів Української держави та
одночасно міністру внутрішніх справ цього уряду. Розпочавши службу колезьким
регістратором, він, завдяки своєму таланту та організаторським здібностям, доріс до
дійсного статського радника, а після Лютневої революції 1917 р. активно співпрацював
з Українською Центральною Радою та гетьманом П. Скоропадським. Статья посвящается Фёдору Андреевичу Лизогубу – украинскому политическому
и общественному деятелю, меценату, председателю Совета Министров Украинской
державы и одновременно министру внутренних дел этого правительства. Начав
службу коллежским регистратором, он, благодаря своему таланту и организаторским
способностям, дорос до действительного статского советника, а после Февральской
революции 1917 г. активно сотрудничал с Украинской Центральной Радой и гетманом П. Скоропадским. When we look at the life journey of Fedir Andriyovych Lyzohub, we have no doubts
that as a statesman, public figure and philanthropist, he takes a place of honor being a person
who played an important role not only in establishment and actions of the Ukrainian
state, but, like the Lyzohubs family in general, he has left an important legacy in history
of Ukrainian society. In December 1893, he started his career as a collegiate registrar
(14th grade in the Table of Ranks of Imperial Russia) at the position of an assistant to the
Secretary of the Congress of magistrates (institution of appeal for first instance courts in
Imperial Russia). In a little while, he was promoted to the position of a state councilor (4th
grade in the Table of Ranks of Imperial Russia). Fedir Lyzohub demonstrated his special
skills of a good manager when he was appointed as Chairman of a district council in Poltava
Guberniya (region) (a highest administrative unit in Imperial Russia).
During the First World War, he was a chief clerk of the Lieutenant General of the
Caucasus region. The 1917 February revolution changed dramatically Fedir Lyzohub’s
life and determined his future, as he got involved into revolutionary events. When the
Central Rada of Ukraine (revolutionary government) was established, he resigned from
the department of Provisional government and arrived in Kyiv where he joined the General
Secretariat of the Central Rada of Ukraine. With Hetman Skoropadsky’s coming to power,
Fedir Lyzohub became one of the ministers of the Ukrainian state. The Bolsheviks’ coup
d’état in Saint Petersburg and political situation in the country forced Fedir Lyzohub to
move from Kyiv and emigrate the country where he would never return again. In 1928,
Fedir Lyzohub died in emigration in the city of Belgrad.